2008
DOI: 10.1002/syn.20535
|View full text |Cite
|
Sign up to set email alerts
|

Reuptake of L‐DOPA‐derived extracellular DA in the striatum of a rodent model of Parkinson's disease via norepinephrine transporter

Abstract: To determine the role of norepinephrine transporter in reuptake of L-DOPA-derived extracellular DA in the DA-denervated Parkinsonian striatum, we examined extracellular DA levels in the striatum of 6-hydroxyDA-lesioned rats that received L-DOPA (50 mg/kg with 12.5 mg/kg of benserazide) and L-DOPA plus desipramine (25 mg/kg), a selective norepinephrine reuptake inhibitor, using in vivo microdialysis. The pretreatment with desipramine increased levels of extracellular DA derived from administrated L-DOPA in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 20 publications
2
38
1
Order By: Relevance
“…Increased extracellular DA in DAdenervated striatum is observed following DMI (Arai et al, 2008). This finding is congruent with our observations that reuptake of DA, derived from L-DOPA, may be modulated by NET.…”
Section: Norepinephrine Transporter and L-dopa Dyskinesiasupporting
confidence: 92%
“…Increased extracellular DA in DAdenervated striatum is observed following DMI (Arai et al, 2008). This finding is congruent with our observations that reuptake of DA, derived from L-DOPA, may be modulated by NET.…”
Section: Norepinephrine Transporter and L-dopa Dyskinesiasupporting
confidence: 92%
“…Importantly, DA is a better substrate for NET, and NET plays a critical role in DA clearance in brain regions where DAT levels are low. In addition, NET also plays a role in striatal DA clearance in the absence of DA innervation (50,82). Cocaine up-regulation of NET is evident in both the PFC and NAc, which are important brain regions in the mesolimbic reward pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In cerebral areas in which DAT levels are low, such as the frontal cortex, NET can reuptake dopamine [8386]. A recent study suggested that L-DOPA-derived dopamine could be uptaken by NET in the striatum of 6-OHDA-lesioned rats because of an increase in dopamine levels following desipramine administration [87]. However, as displayed in Table 1, desipramine exhibits high affinity at SERT and is thus not selective for NET, raising doubt on the authors' conclusions.…”
Section: Monoamine Transportersmentioning
confidence: 99%